Thermal Capacitive Electrochemical Cycle on Carbon-Based Supercapacitor for Converting Low-grade Heat to Electricity - Wang, Xun; Feng, Shien-Ping (Frontiers in Mechanical Engineering, 2017)
It is a great challenge to efficiently convert low-grade heat (<100 oC) to electricity. Currently available heat-to-current converters, such as thermoelectric generators, operating in a low-grade heat regime reach efficiencies no higher than a few percent (<3%). Herein, we illustrated a thermal capacitive electrochemical cycle (TCEC) using electrochemical cell, where the connection to the hot or cold reservoirs alternates in a cyclic charging-heating-discharging-cooling mode to convert heat into electricity, which performs as an electrochemical heat engine. TCEC technology is a cost-effective method for exploiting the temperature-dependent electrostatic potential in an electric double layer (EDL) at carbon electrode/electrolyte interfaces; it produces net electricity by altering the EDL thickness via heating and cooling. In this paper, TCEC on supercapacitor was confirmed on commercial supercapacitor, which showed a poor conversion efficiency. To improve the performance, we redesigned the cell by employing the pouch cell setup with activate carbon as electrode materials and homemade temperature controlling system, which boosted the efficiency from 0.5% of commercial supercapacitor to 3.05% when cycling between 10 oC and 65 oC. A higher efficiency of 3.95% could be reached by using microwaved exfoliated graphene nanosheets (MEG) and nitric acid treated MEG, which could help in decreasing the energy loss caused by charge leakage.